The Effect of Fermentation Time and The Concentration of Sugar on Quality of The Watermelon Peel Candy - Gokma Siregar; Setyohadi Setyohadi; Ridwansyah Ridwansyah (Universitas Sumatera Utara, 2016)
This research was conducted to determine the process of making watermelon peel candy with fermentation time and sugar concentration. This research was performed in April-juni 2012 at the laboratory of Food Technology, Agricultural Faculty.This research was using a factorial completely randomized design with two factors: the concentration of sugar (G1: 50%, G2: 55%, G3: 60%, G4: 65%) and fermentation time (S1: 24 hours, S2: 48 hours , S3: 72 hours, S4: 96 hours). Parameters observed the water content, vitamin C content, crude fiber content, total soluble solid, pH, organoleptics (color, arom, taste) and hardness.The results showed that the sugar concentrations had highly significant effect on water content, levels of vitamin C, total soluble solid, and organoleptic aroma, on the fiber content and pH. Fermentation time had highly significant effect on pH, vitamin C content, aroma, flavor and hardness and had no significant effect water content, fiber content, total soluable solid, and color. Interaction of sugar concentration flavor and color, as well as hardness, and had no significant effect and fermentation time had notdifferent effect on water content, vitamin C content, crude fiber content, total soluble solid, pH, organoleptics (color, aroma, taste) as well as hardness. Keywords: Candy, Fermentation ,Sugar Concentration, Watermelon Peel.